Development and validation of the WhatsApp Negative Impact scale (WANIS) - Bernal-Ruiz, Cristina; Rosa-Alcázar, Ángel; González-Calatayud, Víctor (Anales de Psicología / Annals of Psychology, 2019)
The use of instant messaging affects different areas of users’ daily lives (personal, social, family, work). The aim of this research was to develop and validate a scale that measures the negative impact of WhatsApp's use in several areas (WANIS). Two studies were conducted. The first one was a pilot study in which the scale was built. The sample consisted of 95 university students aged between 17 and 27. (M = 21.34; SD = 2.11). In the second study, the factor structure was examined and the validity of the scale was analysed from a sample of 630 university students aged between 18 and 62 (M = 21.23; DT = 4.32). The exploratory factor analysis revealed that the three-factor solution was most appropriate for interpreting the scale. The instrument had high reliability and good convergent and discriminant validity. The results indicated that sex, marital status and employment status affected the negative impact experienced by WhatsApp users. This scale has proven to be a valid tool for assessing the impact that this instant messaging application has on controlling intimate relationships, the negative consequences of its use and the problematic use by users.